Mass transfer of cadmium ions in a hollow-fiber module by pertraction - Marchese, Jose (2004)
The facilitated transport of Cd(II) ions through a hollow-fiber-supported liquid membrane with bis-2-ethylhexyl phosphoric acid as carrier was studied. The mass transfer rate, expressed as permeability P, was measured as a function of mean aqueous solution velocity and carrier concentration. Characteristic ion permeabilities of 10-26×10-7m/s were measured at feed velocities between 1×10-2-19×10-2 m/s at stripping velocities between 0.22×10-2-7×10-2 m/s with constant feed flow. The measured permeabilities were compared to generally accepted mass transfer correlations. The predicted permeabilities adequately fit the experimental data, indicating that the rate limiting step in the transport of the ion was the diffusion through both aqueous films, feed and stripping, whereas the organic resistance of the membrane was negligible. Furthermore, the proposed model allowed the prediction of the permeability of cadmium for different experimental conditions, which is useful to perform experiments to reduce metal levels in water or other effluents.